Complete graph K4 decomposition into circuits of length 4 - Mohd Darus, Maizon; Ibrahim, Haslinda; Karim, Sharmila; Omar, Zurni; Ahmad, Nazihah (2014)
This paper aims to propose a new method in decomposing Kn into circuits. Our method introduces two new strategies: Wing Strategy (WinS) and Endpoint Strategy (Endp-S).WinS contains first wing and second wing, while Endp-S contains first endpoint and second endpoint.The crucial task for generating circuits in WinS is two vertices of K4 are fixed to be the first wing, meanwhile in Endp-S, the vertices of the first wing are then put into the first endpoint, consecutively.Once the set of circuits are produced from these strategies, the drawing of that circuits can be obtained.